Experimental and theoretical study of the effect of particle size on the forward propagation of smoldering coal. (15th March 2022) - Tang, Yibo; Huang, Wanqi
Highlights: Minimum airflow for smoldering of coal with different rank is 0.13–0.20 m 3 h -1 kg −1 . Positive linear correlation for smoldering spread rate and coal particle sizes. Smoldering propagation rate: Yunnan lignite > Shanxi anthracite > Shanxi bituminous coal. A mathematical model for smoldering propagation on particle size was built. Moisture is dominate factor affecting the spread rate of evaporation front. Abstract: To effectively prevent and control smoldering fires in underground coalmines, the forward propagation of the smoldering process was investigated for three types of coals with different ranks (Yunnan lignite, Shanxi anthracite, Shanxi bituminous coal) and five particle sizes (0.15–0.18 mm, 0.18–0.25 mm, 0.25–0.38 mm, 0.38–0.83 mm and 0.83–1.70 mm) . This was done using both simulations and microstructure testing. The results show that with the reduction of particle size, the proportion of pores > 10 nm increases by 34.0%, the specific surface area increases by 30.0%, and the pore volume increases by 78.8%. The increase of these characteristics is responsible for the strong smoldering capability of coal. The coal samples show four distinct combustion stages (t0 -t4 ) between 25.0 °C and 800.0 °C. With decreasing particle size from 0.83 to 1.70 mm to 0.15–0.18 mm, the activation energy for coal smoldering during the moisture-evaporation stage decreases by 8.2–28.9%, while it decreased by 5.7–16.1% during the combustion/weightlessness stage. The critical minimum air-supply for smoldering coal is 0.13 m 3 h -1 kg −1 to 0.20 m 3 h -1 kg −1 . The critical quantity increases with increasing particle size. The maximum smoldering temperatures peak at 608.0 ℃ to 696.0 ℃ for Shanxi bituminous coal, at 543.1 ℃ to 675 ℃ for Shanxi anthracite, and at 427.0 ℃ to 489.7 ℃ for Yunnan lignite. The spread rate of the moisture-evaporation front can be ranked as follows: Shanxi bituminous coal > Shanxi anthracite > Yunnan lignite. The moisture content is the dominant factor for smoldering spread during this stage. In addition, the spreading rates of the char-oxidation and peak-temperature fronts can be ranked as follows: Yunnan lignite > Shanxi anthracite > Shanxi bituminous coal. The order is mainly affected by the char-oxidation temperature. In addition to the peak temperature, the spread rate for moisture-evaporation front, char-oxidation front, and the peak-temperature front also increases with decreasing particle size from 0.83 to 1.70 mm to 0.15–0.18 mm.